Macroeconomic Factors Affecting the Diffusion of Genetically Modified Crops Technology - Yoah, Nyingchia Yvette (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Genetic modified crop technology is one of the world subject today especially because of food security. The Food and Agricultural Organization (FAO) has food security as one of the most pressing problem found in the world due to the unexpected increase in the world population. Therefore discoveries were made on how to improve on the food security of the world and reduce hunger in the world. One of the solutions was first of all the green revolution which began in India .This revolution helped to improve on the food supply in India and reduced hunger in India as well. Following this revolution was now the genetic modified crop technology which helped to fight against pest and some insects which could destroy some crops. Also some genetic modified cops could grow in some desert areas like in Sub Sahara areas were because of the dryness and harsh weather some crops couldn’t adapt. Due to the advantages discovered from using the genetic modified crop technology, many countries there decided to adopt this technology. The question is therefore why the spread of this technology faster in some countries than other counties? The study tries to develop and test a model which tries to explain the uneven diffusion of genetic modified crop technology across countries. We used mostly macroeconomic factors as our independent variables such as openness to trade, credit availability, GDP per capita, government size, growth rate and inflation. Genetic modified crop land size is our dependent variable. Also we used 10 countries and nine years (2004 -2012) with the help of panel data in our regression. However, the results shows some macroeconomics factors such as credit availability, government size, growth rate were significant in explaining the uneven diffusion of genetically modified crop technology. Keywords: Genetic modified crop technology, Government size, credit availability, openness to trade ,growth rate ,inflation , GDP per capita ,Food security.

ÖZ : Genetik modifiye kırpma teknolojisi nedeniyle özellikle gıda güvenliği, bugün dünya konularından biridir. Gıda ve Tarım Örgütü (FAO) nedeniyle dünya nüfusunun beklenmedik artış, dünyanın bulunan en önemli sorunlardan birisi olarak gıda güvenliğine sahiptir. Bu nedenle keşifler dünya gıda güvenliği geliştirmek ve dünyada açlığı azaltmak için nasıl yapılmıştır. Çözümlerden biri Hindistan'da gıda kaynağı geliştirmek için yardımcı oldu ve aynı zamanda Hindistan'da açlık azaltılmış Hindistan .Bu devrim başladı tüm yeşil devrimin ilk oldu. Bu devrim sonrasında artık haşere ve bazı bitkileri yok edebilecek bazı böceklere karşı mücadele için yardımcı genetik modifiye bitki teknolojisi oldu. Ayrıca bazı genetik modifiye polisler Alt Sahra alanları nedeniyle kuruluk ve bazı bitkileri adapte olabilir sert hava vardı gibi bazı çöl bölgelerinde büyümeye başladı. Genetik modifiye bitki teknolojisini kullanarak keşfetti avantajları, birçok ülke var, bu teknolojiyi benimsemeye karar verdi. Soru nedenle neden diğer ilçeleri göre bazı ülkelerde bu teknolojinin daha hızlı yayılması? Çalışma ülkeler arasında genetik modifiye bitki teknolojisinin düzensiz difüzyon açıklamaya çalışan bir modeli geliştirmek ve test etmek için çalışır. Biz ticaret açıklık, kredi durumu, kişi başına düşen GSYİH, hükümet boyutu, büyüme oranı ve enflasyon gibi bizim bağımsız değişkenler olarak çoğunlukla makroekonomik faktörler kullanılır. Genetik modifiye kırpma arazi büyüklüğü bizim bağımlı değişkendir. Ayrıca 10 ülke ve bizim regresyon panel veri yardımıyla dokuz yıl (2004 -2012) kullanılır. Ancak sonuçlar, kredi durumu, hükümet boyutu gibi bazı makroekonomi faktörler gösterir, büyüme oranı genetiği değiştirilmiş bitki teknolojisinin düzensiz difüzyon açıklayan önemli idi. Anahtar Kelimeler : Genetik modifiye kırpma teknolojisi , Hükümet boyutu , kredi kullanılabilirliği , ticaret açıklık , büyüme oranı , enflasyon , kişi başına GSYİH , Gıda güvenliği
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2015. Supervisor: Assist. Prof. Dr. Çağay Coşkuner.
Keywords: Economics; Genetically modified foods - Economic Aspects; Genetic modified crop technology; Government size; credit availability; openness to trade; growth rate; inflation; GDP per capita; Food security